Amino terminal peptides from the Plasmodium falciparum EBA-181/JESEBL protein bind specifically to erythrocytes and inhibit in vitro merozoite invasion (2005)
Several EBA-175 paralogues (EBA-140, EBA-165, EBA-175, EBA-181, and EBL-1) have been described among the Plasmodium falciparum malaria parasite proteins, which are important in the red blood cell (RBC) invasion process. EBA-181/JESEBL is a 181 kDa protein expressed in the late schizont stage and located in the micronemes; it belongs to the Plasmodium Duffy binding-like family and is able to interact with the erythrocyte surface. Here, we describe the synthesis of 78, 20-mer synthetic peptides derived from the reported EBA-181/JESEBL sequence and their ability to bind RBCs in receptor–ligand assays. Five peptides (numbered 30030, 30031, 30045, 30051, and 30060) displayed high specific binding to erythrocytes; their equilibrium binding parameters were then determined. These peptides interacted with 53 and 33 kDa receptor proteins on the erythrocyte surface, this binding being altered when RBCs were pretreated with enzymes. They were able to inhibit P. falciparum merozoite invasion of RBCs when tested in in vitro assays. According to these results, these five EBA-181/JESEBL high specific erythrocyte binding peptides, as well as the entire protein, were seen to be involved in the molecular machinery used by the parasite for invading RBCs. They are thus suggested as potential candidates in designing a multi-sub-unit vaccine able to combat the P. falciparum malaria parasite.